Profesionalisme Guru PAK dalam Pengimplementasian Kurikulum - Fransisca Hasugian; Darmayanty; Meilan pakpahan; Lesti simanjuntak; Elsyanti Gultom; Hisardo Sitorus (Journal of Mandalika Literature, 2025)
This research aims to determine the professionalism of Christian Religious Education (PAK) teachers in implementing the curriculum. Using descriptive qualitative methods, this research found that Christian religious education is an education that focuses on the Lord Jesus Christ who uses the pulpit as a communication tool to introduce people to Christ with the help of the Holy Spirit. Christian religious education is a medium for bringing believers together with Jesus Christ so that they can truly know Jesus Christ personally. The professionalism of Christian Religious Education teachers greatly influences the success of curriculum implementation. The main influencing factors include pedagogical competence, mastery of material, and the ability to adapt learning to student needs. Apart from that, managerial support, facilities and competency development policies are also important. In conclusion, a deep understanding of the curriculum, appropriate learning design, and the use of relevant methods and technology are very necessary for effective implementation.